2019
DOI: 10.1111/jvim.15512
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐free amino acid profiles in dogs with hepatocellular carcinoma

Abstract: Background Metabolomic analysis using blood samples has been suggested to be useful for the early detection of cancer. Among metabolites, plasma‐free amino acid (PFAA) profiles are potential diagnostic biomarkers for several diseases including cancer. However, the relationship between PFAA concentrations and liver tumors in dogs remains unknown. Objective To determine the characteristics of PFAA profiles of dogs with hepatocellular carcinoma (HCC) and correlated clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…27 In a recent study in which amino acid profiles of dogs with congenital PSS, dogs with chronic hepatitis, and healthy dogs were analyzed, serum concentrations of BCAAs were significantly lower whereas serum concentrations of tyrosine and phenylalanine (both AAAs) were significantly higher, leading to a lower BCAA-to-AAA ratio in dogs with congenital PSS compared to healthy dogs and dogs with chronic hepatitis. 13 Although both tyrosine and phenylalanine concentrations were very high at diagnosis in our study, all BCAAs were at the lower end of the reference range reported in dogs, 18,19,[28][29][30] which is consistent with previous studies. [11][12][13] Although valine significantly increased after surgical attenuation, it remained within normal limits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…27 In a recent study in which amino acid profiles of dogs with congenital PSS, dogs with chronic hepatitis, and healthy dogs were analyzed, serum concentrations of BCAAs were significantly lower whereas serum concentrations of tyrosine and phenylalanine (both AAAs) were significantly higher, leading to a lower BCAA-to-AAA ratio in dogs with congenital PSS compared to healthy dogs and dogs with chronic hepatitis. 13 Although both tyrosine and phenylalanine concentrations were very high at diagnosis in our study, all BCAAs were at the lower end of the reference range reported in dogs, 18,19,[28][29][30] which is consistent with previous studies. [11][12][13] Although valine significantly increased after surgical attenuation, it remained within normal limits.…”
Section: Discussionsupporting
confidence: 92%
“…Liver diseases, however, are very diverse, and amino acid profiles found in dogs with different types of liver diseases vary markedly 18,28 . Dogs with focal liver masses have higher plasma glutamic acid concentrations compared to age‐matched healthy dogs regardless of whether the lesions were benign or hepatocellular carcinomas, and plasma glutamic acid concentrations were not significantly different 3 to 6 months after surgical resection of hepatocellular carcinomas 18 . Dogs with superficial necrolytic dermatitis (also called hepatocutaneous syndrome) have mean plasma amino concentrations that are significantly lower than those of dogs with acute and chronic hepatitis, most likely because of increased hepatic catabolism 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is expected that the amino acids balance was broken in hepatic disease such as fatty liver disease, 7 cirrhosis 8 and liver cancer. 9 Triptolide (TP, its structure is shown in Figure 1), a cyclooxidized diterpene lactone, is a major active ingredient isolated from Tripterygium wilfordii Hook. F, 10 which has great potential in the treatment of rheumatoid arthritis 11 and cancer.…”
Section: Introductionmentioning
confidence: 99%